An open-source package with interactive Jupyter Notebooks to enhance the accessibility of reservoir operations simulation and optimisation. (November 2021) - Peñuela, Andres; Hutton, Christopher; Pianosi, Francesca
Abstract: In this paper we present the interactive Reservoir Operations Notebooks and Software (iRONS) toolbox for reservoir modelling and optimisation. The toolbox is meant to serve the research and professional community in hydrology and water resource management and contribute to bridge the gaps between them. iRONS is composed of a package of Python core functions and a set of interactive Jupyter Notebooks. Core functions implement typical reservoir modelling tasks and the interactive Jupyter Notebooks illustrate, with practical examples, the key functionalities of iRONS. We describe our development philosophy, the key features of iRONS, and report some results of evaluating the effectiveness of interactive Jupyter Notebooks for training and knowledge transfer. The paper may be of interest also beyond the water resources management field, as an example of how Jupyter Notebooks and interactive visualisation help improving the documentation and sharing of open-source code and the communication of underpinning methodologies. Highlights: We present a Python package, iRONS, for reservoir operations simulation and optimisation. We discuss our development philosophy of modularity, minimalism, openness and accessibility. We evaluate the use of interactive Jupyter Notebooks for documentation and training.